Influenza vaccine concurrently administered with a combination measles, mumps, and rubella vaccine to young children - Lum, L.C.S.; Borja-Tabora, C.F.; Breiman, R.F.; Vesikari, T.; Sablan, B.P.; Chay, O.M.; Tantracheewathorn, T.; Schmitt, H.J.; Lau, Y.L.; Bowonkiratikachorn, P.; Tam, J.S.; Lee, B.W.; et al. (Elsevier, 2010)
Children aged 11 to <24 months received 2 intranasal doses of live attenuated influenza vaccine (LAIV) or placebo, 35 +/- 7 days apart. Dose 1 was administered concomitantly with a combined measles, mumps, and rubella vaccine (Priorix). Seroresponses to measles and mumps were similar between groups. Compared with placebo, response rates to rubella in LAIV+Priorix recipients were statistically lower at a 15IU/mL threshold (83.9% vs 78.0%) and the prespecified noninferiority criteria were not met. In a post hoc analysis using an alternate widely accepted threshold of 10IU/mL, the noninferiority criteria were met (93.4% vs 89.8%). Concomitant administration with Priorix did not affect the overall influenza protection rate of LAIV (78.4% and 63.8% against antigenically similar influenza strains and any strain, respectively). (C) 2009 Elsevier Ltd. All rights reserved.